Interactions between Iron and Nickel in Fe-Ni Nanoparticles on Y Zeolite for Co-Processing of Fossil Feedstock with Lignin-Derived Isoeugenol - Vajglová Zuzana; Gauli Bibesh; Mäki-Arvela Päivi; Kumar Narendra; Eränen Kari; Wärna Johan; Lassfolk Robert; Simakova Irina L; Prosvirin Igor P; Peurla Markus; Lindén Johan Kaarle Mikael; Huhtinen Hannu; et al. (AMER CHEMICAL SOC, 2025)
A set of low-cost monometallic Fe, Ni, and bimetallic Fe-Ni bifunctional H-Y-5.1 catalysts with different metal ratioswere synthesized by sequential incipient wetness impregnation. The catalysts were characterized in detail by N-2 physisorption,Fourier transform infrared spectroscopy with pyridine, inductively coupled plasma optical emission spectroscopy, X-ray diffraction (XRD),transmission and scanning electron microscopy (TEM-SEM), magicangle spinning nuclear magnetic resonance, X-ray photoelectron spectroscopy(XPS), Mössbauer spectroscopy, magnetic measurements, temperature-programmed reduction (TPR), and X-ray absorption spectroscopy (XAS). The results revealed that introduction of Fe led to a decrease of strong acid sites and an increase of medium Bronsted acid sites, while introduction of Ni increased the number of Lewis acid sites. The particle sizeof iron was approx. 5 nm, being ca. fourfold higher for nickel. XPS demonstrated higher iron content on the catalyst surface compared to nickel. Both Mö'ssbauer spectroscopy and magnetic measurement confirmed the ferromagnetic behavior of all catalysts. In addition,the results from XRD, TEM, XPS, XAS, and magnetization suggested strong Fe-Ni nanoparticle interactions, which were supported by modelingof TPR profiles. Catalytic results of the co-processing of fossil feedstock with lignin-derived isoeugenol clearly showed that bothproduct distribution and activity of Fe-Ni catalysts strongly depend on the metals' ratio and their interactions. Key properties affected by the Fe-Ni metal ratio, which played a positiverole in co-processing, were a smaller medial metal nanoparticle size(<6 nm), a lower metal-acid site ratio, as well as presencein the catalyst of fcc FeNi alloy structure and fcc Ni doped withFe.